A Review Paper on e-service; Technology Concepts. (2015) - Taherdoost, Hamed; Sahibuddin, Shamsul; Jalaliyoon, Neda
Abstract: Recent growth in information technology has set the pace for an electronic revolution leading to emergence of electronic services. Business to consumer e-service assists organizations to decrease costs, speed up delivery time and serve more customers. Therefore, many enterprises have already moved or planning to move their services and goods to the electronic environment. In this regard, it is crucial to recognize the characteristics of each type of products and services. The main goal of this research is to provide an extensive review and gather conceptual perspectives of electronic services. In order to understand the nature of electronic services it is essential to explore the characteristics, advantages and barriers of e-services. This study sets theoretical and research foundation for future empirical researches by differentiates of service and e-service features and furthermore categorization of e-service users.